Hydrocephalus - Water on the Brain 2018
DOI: 10.5772/intechopen.73302
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and Characterization of Cerebrospinal Fluid Motion Based on Magnetic Resonance Imaging

Abstract: Purpose: To characterize cardiac-and respiratory-driven cerebrospinal fluid (CSF) motions in intracranial space noninvasively, four-dimensional velocity mapping (4D-VM), correlation mapping, and power and frequency mapping with cardiac-gated and/or asynchronous magnetic resonance (MR) phase contrast (PC) techniques were conducted. Methods: Cardiac-gated PC in three spatial directions was applied to young, healthy, elderly, healthy, and idiopathic normal pressure hydrocephalus patient groups. 4D-VM was created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In contrast, for the amount of volume displacement, the respiratory component was greater. 25 This pattern of fast and small cardiac-driven modulations but slow and high displacement by respiration was confirmed by the study of Yatsushiro et al 26 Yildiz et al were able to demonstrate a comparable contribution of respiration and cardiac pulsations on CSF dynamics through the aqueduct during deep breathing but not during natural breathing. 27 This pattern could resemble the situation during deep nonrapid eye movement (NREM) sleep.…”
Section: Breathing Csf Dynamics and Venous Flowmentioning
confidence: 62%
“…In contrast, for the amount of volume displacement, the respiratory component was greater. 25 This pattern of fast and small cardiac-driven modulations but slow and high displacement by respiration was confirmed by the study of Yatsushiro et al 26 Yildiz et al were able to demonstrate a comparable contribution of respiration and cardiac pulsations on CSF dynamics through the aqueduct during deep breathing but not during natural breathing. 27 This pattern could resemble the situation during deep nonrapid eye movement (NREM) sleep.…”
Section: Breathing Csf Dynamics and Venous Flowmentioning
confidence: 62%
“…Material property values used in MREf are summarized in Table 1. Bulk density was chosen to be similar to brain tissue, while fluid density and dynamic viscosity were selected to fall in the range of cerebrospinal fluid [96][97][98][99][100]. The apparent density is a coarse grained effective quantity coming from the interactions between the fluid and the pore space, and we chose a value based on prior studies, noting that a low sensitivity of results to ρ a was demonstrated [34][35][36]68].…”
Section: Forward Problemmentioning
confidence: 99%
“…This interplay might be challenged by the endurance of space flight microgravity in contrast to the terrestrial environment, in which strong upward CSF movement can be observed only sporadically during single phases of NREM sleep and during phases of spontaneous forced breathing (Dreha‐Kulaczewski et al., 2017; Ludwig et al., 2020). The propulsion of CSF primarily by deep breathing, as opposed to the small and fast oscillations driven by the heartbeat, was a common observation in several MRI experiments, in which physiological cardiac gating by real‐time methods enabled the effect of the pulse to be excluded (Takizawa et al., 2017; Yatsushiro et al, 2018; Yildiz et al., 2017). The review at hand will focus on these elements and provisions and will identify related concepts.…”
Section: Ciliary Functionmentioning
confidence: 99%